2009
DOI: 10.1111/j.1440-1746.2009.05848.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestations and survival of hepatocellular carcinoma patients with peritoneal metastasis

Abstract: Peritoneal metastases of HCC are rare and can occur synchronously or metachronously. Though increased long-term survival was found in patients who had surgical removal of peritoneal metastases, the main determinant of better survival is Child-Pugh grade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
63
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 21 publications
3
63
0
Order By: Relevance
“…PR in HCC is uncommon. The reported incidence ranged 2–16% 11–14,31. In our series, the PR rate was 3.0%.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…PR in HCC is uncommon. The reported incidence ranged 2–16% 11–14,31. In our series, the PR rate was 3.0%.…”
Section: Discussionmentioning
confidence: 43%
“…Peritoneal implantation in HCC is uncommon, with reported incidences ranging 2–16% 11–14. Generally, peritoneal recurrence (PR) in HCC was considered to be an incurable terminal disease.…”
mentioning
confidence: 99%
“…These two factors are already well-known factors determining overall survival in HCC patients without extrahepatic metastasis [15][16][17]26]. Moreover, some studies have suggested these two factors as prognostic factors even in HCC patients with extrahepatic metastasis, though the incidence of PM in such studies is rare [5,21,27]. These results emphasize the importance of continuous treatment of intrahepatic tumor, even in the presence of distant metastasis, and the need for supportive care to maintain better hepatic function to prolong overall survival in HCC patients with PM.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with lung metastasis, control of the primary HCC was also an important predictor of survival, though the lung metastasis itself can cause respiratory failure which may lead to the fatal outcome [18][19][20]. However, there are few reports on the prognosis of HCC patients with PM, probably because of the low incidence of PM in HCC patients [21].…”
Section: Introductionmentioning
confidence: 99%
“…Literature is very scarce in this field [6,8,9]; in the published studies, HCC-PPL is generally considered together with other extrahepatic localizations [10,11]. Furthermore, the largest surveys and few multicentric reviews available are oriented toward the risk of seeding after the different percutaneous procedures rather than toward the descriptions of the natural history of these patients [12][13][14].…”
Section: Introductionmentioning
confidence: 99%